Lossless Dynamic Models of the Quasi-Z-Source Converter Family - Vinnikov, Dmitri; Husev, Oleksandr; Roasto, Indrek (Electrical, Control and Communication Engineering, 2011)
This paper is devoted to the quasi-Z-source (qZS) converter family. Recently, the qZS-converters have attracted attention because of their specific properties of voltage boost and buck functions with a single switching stage, which could be especially beneficial in renewable energy applications. As main representatives of the qZS-converter family, the traditional quasi-Z-source inverter as well as two novel extended boost quasi-Z-source inverters are discussed. Lossless dynamic models of these topologies are presented and analyzed.